2021
DOI: 10.1021/acs.joc.1c00598
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photoswitching Properties of Bioinspired Dissymmetric γ-Pyrone, an Analogue of Cyclocurcumin

Abstract: Cyclocurcumin (CC), a turmeric curcuminoid with potential therapeutic properties, is also a natural photoswitch that may undergo E/Z photoisomerization under UV light. To be further exploited in relevant biological applications, photoactivation under near-infrared (NIR) irradiation is required. Such requirement can be met through opportune chemical modifications, by favoring two-photon absorption (TPA) probability. Herein, a general and efficient synthesis of a biomimetic 2,6disubstituted-γ-pyrone analogue of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 55 publications
4
34
0
Order By: Relevance
“…Coherently with the GAFF protocol, and with our previous works, [41][42][43] the electrostatic procedure has been obtained from the Hartree-Fock wavefunction obtained with the 6-31G basis set. Note that the ground state geometry of the chromophore in its trans and cis configuration was previously optimized at Density Functional Theory (DFT) level using B3LYP functional and the 6-31+G* basis set.…”
Section: General MD Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coherently with the GAFF protocol, and with our previous works, [41][42][43] the electrostatic procedure has been obtained from the Hartree-Fock wavefunction obtained with the 6-31G basis set. Note that the ground state geometry of the chromophore in its trans and cis configuration was previously optimized at Density Functional Theory (DFT) level using B3LYP functional and the 6-31+G* basis set.…”
Section: General MD Simulationsmentioning
confidence: 99%
“…[50][51][52][53] We have also shown that by introducing a g-pyrone analogous not only the absorption wavelength is red-shifted, as well the isomerization solvent-dependency is strongly reduced. 41,42 Finally, by using a combination of experimental and modeling techniques, including enhanced sampling and free energy calculations, we have shown that appending the g-pyrone derivative with a hydrophobic butyl chain (CCBu, Figure 1) leads to the spontaneous penetration inside the lipid bilayer, and more specifically at the interface between the polar heads and the fatty acid core. 54 Interestingly, the free energy profile for the insertion into the bilayer shows important differences between the trans and the cis isomers, with the former developing a more favorable interaction with the lipid bilayer.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In some previous contributions we have shown that natural curcumin and cyclocurcumin may indeed act as molecular photoswitches, undergoing E to Z isomerization under visible light irradiation. [30][31][32] However, in these natural compounds, the isomerization is pretty slow and its chemical quantum yield is strongly environment dependent due to the competition between np* and pp* excited states. 33 As a matter of fact, curcumin may also show interesting properties in term of 1 O 2 generation, due to its efficient intersystem crossing (ISC) coupled with residual fluorescence, which may facilitate its cellular localization.…”
mentioning
confidence: 99%
“…33 As a matter of fact, curcumin may also show interesting properties in term of 1 O 2 generation, due to its efficient intersystem crossing (ISC) coupled with residual fluorescence, which may facilitate its cellular localization. 34,35 Recently, 32 we have shown that by opportunely modifying the chemical core of cyclocurcumin, by replacing the 2,3-dihydropyran-4-one core by a 2-6-substitued g-pyrone (Figure 1), the photoisomerization efficiency is strongly enhanced whatever the medium. Experimental findings have also been rationalized and supported by the calculation of the PES of the most important excited state for the natural-occurring and the biomimetic compound.…”
mentioning
confidence: 99%